Comparison of four layouts of optimized triple-pressure heat recovery steam generator - Somchart Chantasiriwan (Case Studies in Thermal Engineering)
Triple-pressure heat recovery steam generators are found in various sizes of combined cycle power plants. A triple-pressure heat recovery steam generator consists of economizers, evaporators, and superheaters at high, intermediate, and low pressures. Typically, reheater is also added for performance enhancement. A layout of a triple-pressure heat recovery steam generator corresponds to an arrangement of these heat exchangers. If the layout of a triple-pressure heat recovery steam generator is known, the optimized steam parameters, which result in the maximum net power output, can be determined for a specified total area of the heat recovery steam generator. A method of optimizing steam parameters of four layouts of triple-pressure heat recovery steam generator is presented in this paper. It is found that standard layout yields the smallest optimal net power output, and the layout in which high pressure superheater is split into two sections yields the largest maximum net power output.